Electrochemical Behaviour Of Ferrocene/Ferricinium Redox System In Pure And CO2 Saturated [C6MIM][PF6] - Chanfreau, Sebastien; He, Liang Nian; Yu, Bing (ASEAN Journal of Chemical Engineering, 2011)
The electrochemical behaviour of ferrocene has been studied in green solvent combining pure ionic liquid and CO2. Experimental results were achieved for the Fc/Fc+ (ferrocene/ferricinium ion) oxidation/reduction in pure and CO2 saturated 1-hexyl-3-methylimidazolium hexafluorophosphate ([C6MIM][PF6]) over the temperature range from 298.15 K to 323.15 K. Peak shaped voltammograms were obtained and usual electrochemical parameters were calculated in order to classify electron process at the electrode. Diffusion coefficients of electroactive species were determined in the order of 10-11 m2 s-1 using the Randles–Ševcík relationship. Mass transport was also favoured by both increases in temperature and dilution of CO2 in the media.